2023
DOI: 10.1002/adhm.202300064
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Bioactive Glasses Composite Promotes Angiogenesis by the Synergistic Effect of Wireless Electrical Stimulation and Active Ions

Abstract: Insufficient angiogenesis frequently occurs after the implantation of orthopedic materials, which greatly increases the risk of bone defect reconstruction failure. Therefore, the development of bone implant with improved angiogenic properties is of great importance. Mimicking the extracellular matrix clues provides a more direct and effective strategy to modulate angiogenesis. Herein, inspired by the bioelectrical characteristics of the bone microenvironment, a piezoelectric bioactive glasses composite (P‐KNN/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This suggests that EF may be the primary factor promoting angiogenesis in regenerated tissue. Previous reports have shown that EFs can enhance endothelial cell adhesion, migration, and differentiation by activating the eNOS/NO signaling pathway [52][53], and low-intensity EFs can promote tissue angiogenesis by stimulating the VEGFR signaling pathway. Consequently, low-voltage electrical stimulation generated during the charging and discharging of capacitive dressings not only exhibits potent antibacterial activity but also enhances vascularization of regenerated tissues, thereby facilitating wound healing.…”
Section: Histological Analysismentioning
confidence: 96%
“…This suggests that EF may be the primary factor promoting angiogenesis in regenerated tissue. Previous reports have shown that EFs can enhance endothelial cell adhesion, migration, and differentiation by activating the eNOS/NO signaling pathway [52][53], and low-intensity EFs can promote tissue angiogenesis by stimulating the VEGFR signaling pathway. Consequently, low-voltage electrical stimulation generated during the charging and discharging of capacitive dressings not only exhibits potent antibacterial activity but also enhances vascularization of regenerated tissues, thereby facilitating wound healing.…”
Section: Histological Analysismentioning
confidence: 96%
“…[ 178 ] Zhai's team observed the apparent ability of piezoelectric composites to promote angiogenesis through experiments on chorioallantoic membrane of chicken embryos (Figure 6d). [ 179 ] They synthesized polarized KNN (PKNN) using piezoelectric bioactive glass (BG) composites (PKNN/BG). PKNN/BG had a higher surface potential (332.04 ± 12.85 mV) than BG and KNN/BG as measured by scanning Kelvin probe force microscopy and was able to provide excellent radiation stimulation to seed human umbilical vein endothelial cells onto its surface.…”
Section: Application Of Piezoelectric Materials To Stimulate Cell Dif...mentioning
confidence: 99%
“…d) In vivo assessment of angiogenesis were, respectively, optical images of CAMs after 5 days of stimulation (gray shaded portions indicate the location where the samples were placed), the total vascular junctions, the total size, the total length, and the survival of chicken embryos. Reproduced with permission [179]. Copyright 2023, WILEY-VCH.…”
mentioning
confidence: 99%
“…fabricated an excellent biocompatible piezoelectric scaffold by combining KNN and BG. By analyzing the expression of endothelial nitric oxide synthase, intracellular calcium levels and changes in cell membrane potential, it was concluded that the scaffold regulates angiogenesis by activating the endothelial nitric oxide synthase/NO signaling pathway under the synergistic effect of electrical stimulation and activating ions, further illuminating the potential mechanisms by which angiogenesis can be promoted [ 253 ].…”
Section: Reviewmentioning
confidence: 99%